PECULIARITIES OF FUNCTIONING OF THE FINANCIAL SYSTEM OF UKRAINE AND ASSET MANAGEMENT IN THE CONTEXT OF MILITARY AGGRESSION - Ustynova, Iryna; Bilyavska, Valeria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the purpose of the study is to review and analyses the legal nature of the financial system of Ukraine, the main aspects and identify the shortcomings that hinder the development of the financial system, to find possible ways to improve it, to analyses the problems and determine the prospects for the functioning of the financial system in modern conditions, namely, under martial law. Research methods: the article uses the following general scientific methods of research: observation and description and theoretical methods: analysis, generalization, explanation, as well as systemic, functional, specific and sociological. Results: particular attention is paid to the formation of budgets that have experienced the greatest pressure and the allocation of financial resources to defense and social needs. In addition, the problems of imbalance between budget expenditures and revenues, as well as the foreign exchange market, which continues to operate with restrictions imposed during martial law, are considered. The article also discusses existing and potential solutions to the problems of the financial system, including their adaptation to the needs of defense and ensuring the smooth functioning of the public finance system. Discussion: the military invasion of Ukraine and globalization processes in the world have led to significant negative changes in the existence of Ukraine’s financial system, and therefore require new practices in addressing the issues of forming the country’s budget, local budgets, significant adjustments to tax legislation and changes in the size of the tax burden. An essential component of solving these issues is to expand cooperation with international financial organizations, to promote the improvement of the investment climate, etc.